Risk factors for hip impact during real-life falls captured on video in long-term care. Issue 2 (February 2016) - Yang, Y.; Mackey, D.; Liu-Ambrose, T.; Feldman, F.; Robinovitch, S.
Abstract Summary Hip fracture risk is increased by landing on the hip. We examined factors that contribute to hip impact during real-life falls in long-term care facilities. Our results indicate that hip impact is equally likely in falls initially directed forward as sideways and more common among individuals with dependent Activities of Daily Living (ADL) performance. Introduction The risk for hip fracture in older adults increases 30-fold by impacting the hip during a fall. This study examined biomechanical and health status factors that contribute to hip impact through the analysis of real-life falls captured on video in long-term care (LTC) facilities. Methods Over a 7-year period, we captured 520 falls experienced by 160 residents who provided consent for releasing their health records. Each video was analyzed by a three-member team using a validated questionnaire to determine whether impact occurred to the hip or hand, the initial fall direction and landing configuration, attempts of stepping responses, and use of mobility aids. We also collected information related to resident physical and cognitive function, disease diagnoses, and use of medications from the Minimum Data Set. Results Hip impact occurred in 40 % of falls. Falling forward or sideways was significantly associated with higher odds of hip impact, compared to falling backward (OR 4.2, 95 % CI 2.4–7.1) and straight down (7.9, 4.1–15.6). In 32 % of sideways falls, individuals rotated to land backward. This substantially reduced the odds for hip impact (0.1, 0.03–0.4). Tendency for body rotation was decreased for individuals with dependent ADL performance (0.43, 0.2–1.0). Conclusions Hip impact was equally likely in falls initially directed forward as sideways, due to the tendency for axial body rotation during descent. A rotation from sideways to backward decreased the odds of hip impact 10-fold. Our results may contribute to improvements in risk assessment and strategies to reduce risk for hip fracture in older adults.